METHODOLOGY FOR THE FORMATION OF PRIMARY PREVENTION OF PARASITIC DISEASES IN PRESCHOOL CHILDREN - Yusupov Sh.R., Ibraximova H.R., Masharipova Sh.S. (KLINIK TADQIQOTLAR VA INNOVATSION TIBBIYOT, 2025)
The aim of the study was the method of formation of primary prevention of parasitic diseases in preschool children.The results of the research showed that in the main group of preschool children, where the program for teaching primary prevention of parasitic diseases was implemented, children with a low level of readiness were 4.06 times less than in the control group, among whose children the program for teaching primary prevention of parasitic diseases was not carried out - respectively, on average 18.53% (n=53) versus 75.19% (n=197). On the contrary, the number of children with an average and high level of readiness was higher in the main group - on average 59.09% (n=169) and 22.38% (n=64), respectively, against 23.28% (n=61) and 1.53% (n=4) in the control group